Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Microbiology of a NaCl stalactite ‘salticle’ in Triassic halite - Thomas P. Thompson; Stephen A. Kelly; Timofey Skvortsov; Gill Plunkett; Alastair Ruffell; John E. Hallsworth; Jason Hopps; Brendan F. Gilmore (Environmental Microbiology, 2021)
Summary Large regions of Earth's surface are underlain by salt deposits that evaporated from ancient oceans and are populated by extreme halophilic microbes. Some of these halophiles may have been preserved over geological timescales within hypersaline fluid inclusions, but ingresses of water and/or anthropogenic activities can lead to the formation of alternative habitats, including NaCl stalactites or other speleothems. While the microbiology of ancient evaporites has been well studied, the ecology of these recently formed structures is less‐well understood. Here, the microbiology of a NaCl stalactite (‘salticle’) in a Triassic halite mine is characterized. The specific aims were to determine the presence of fluid inclusions, determine the microbial structure of the salticle compared with a nearby brine‐pool and surficial soil, and characterize the ecophysiological capabilities of this unique ecosystem. The salticle contained fluid inclusions, and their microbiome was composed of Euryarchaetota, Proteobacteria, and Actinobacteria, with Haloarchaea in greater abundance than brine‐pool or soil microbiomes. The salticle metagenome exhibited a greater abundance of genes involved in osmoregulation, anaerobic respiration, UV resistance, oxidative stress, and stress‐protein synthesis relative to the soil microbiome. We discuss the potential astrobiological implications of salticles as enclosed salt‐saturated habitats that are protected from ionizing radiation and have a stable water activity.